2018
DOI: 10.1002/adma.201802273
|View full text |Cite
|
Sign up to set email alerts
|

A Micro‐Ark for Cells: Highly Open Porous Polyhydroxyalkanoate Microspheres as Injectable Scaffolds for Tissue Regeneration

Abstract: To avoid large open surgery using scaffold transplants, small-sized cell carriers are employed to repair complexly shaped tissue defects. However, most cell carriers show poor cell adherences and viability. Therefore, polyhydroxyalkanoate (PHA), a natural biopolymer, is used to prepare highly open porous microspheres (OPMs) of 300-360 µm in diameter, combining the advantages of microspheres and scaffolds to serve as injectable carriers harboring proliferating stem cells. In addition to the convenient injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
179
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 40 publications
0
179
0
Order By: Relevance
“…George Guo-Qiang Chen's group observed that 3-hydroxybutyrate (3HB) monomers leaking after hydrolysis of implanted PHB promoted calcium deposition and alkaline phosphatase in murine osteoblasts [198]. Wei and colleagues used PHA as porous microparticles as an injectable scaffold for hMSC delivery [199]. These hMSC differentiated in vivo in a mouse model and gave rise to ectopic bone formation.…”
Section: Bioplastics Polymers As Implants In Vivomentioning
confidence: 99%
“…George Guo-Qiang Chen's group observed that 3-hydroxybutyrate (3HB) monomers leaking after hydrolysis of implanted PHB promoted calcium deposition and alkaline phosphatase in murine osteoblasts [198]. Wei and colleagues used PHA as porous microparticles as an injectable scaffold for hMSC delivery [199]. These hMSC differentiated in vivo in a mouse model and gave rise to ectopic bone formation.…”
Section: Bioplastics Polymers As Implants In Vivomentioning
confidence: 99%
“…Small‐molecule‐based in situ reversible heterodimeric nanoswitching offers cytocompatible and minimally invasive control to regulate reversible cell adhesion and release on implanted materials. We subcutaneously implanted (BP‐AuNP)‐grafted substrate into mice and injected hMSCs onto substrate ( Figure A).…”
Section: Methodsmentioning
confidence: 99%
“…Red channel: dead; green channel: live cells. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%
“…Adding to these technologies, open porous microparticle platforms have also received a significant focus for 3D microtissues assembly owing to their improved gases/nutrients and waste metabolites exchange with the surrounding microenvironment. Recently microporous particles technology was advanced with the fabrication of highly open porous polyhydroxyalkanoate (PHA) microspheres (OPMs; 300–360 µm in diameter, Figure B), which are able to harbor stem cells in their interconnected network while also assuring a higher cell viability and continuous proliferation in comparison to their less porous counterparts …”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%